ChemInform Abstract: Stereoselectivity of the Honda—Reformatsky Reaction in Reactions with Ethyl Bromodifluoroacetate with α‐Oxygenated Sulfinylimines. Issue 39 (23rd September 2014) - Fontenelle, Clement Q.; Conroy, Matthew; Light, Mark; Poisson, Thomas; Pannecoucke, Xavier; Linclau, Bruno
Abstract The Honda—Reformatsky reaction involving bromodifluoroacetate (II) is investigated with both sulfinylimines derived from aliphatic aldehydes as well as those derived from aldehydes bearing a chiral α‐oxygenated substituent.